NIPPLE RECONSTRUCTION: DESCRIPTION AND CONTRIBUTION TO FOUR-SQUARE TECHNIQUE OR CYLINDRICAL FLAP - Slaibi Filho, José; Pires, Douglas de Miranda; Andrade, Raffaela Levy de; Valadares, Carolina Nazareth; Figueiredo, Carolina Lamac; Nascimento, Mariana dos Santos (Mastology, 2017)
Introduction: Techniques for breast reconstruction are becoming the new standard of care for breast cancer patients. In this context, reconstruction surgery of the nipple-areolar complex consists of an essential surgical approach to obtain a satisfactory esthetic result. Objectives: The article proposes a modification in a preexisting technique that would have less soft tissue loss and, consequently, better esthetic outcomes. Methods: Four patients underwent reconstruction of the mammary papilla with the technique proposed at Santa Casa de Ilhéus and Santa Casa de Belo Horizonte (SCBH). The technique consists of modifying the four-square flap. De-epithelialization of a lateral wing of the dermatoglossal flap is performed, which will remain in the center of the flap, providing increased central volume and increased vascularization. Results: Patients underwent nipple reconstruction with local anesthesia at least six months after breast reconstruction. They were then evaluated 30 days, 90 days and 180 days after the procedure. The volume and projection of the nipples were evaluated by photographic records. Discussion: There are numerous neo-nipple surgical descriptions, most of them presenting significant volume loss with impairment of body image. Several factors may contribute to nipple flattening after reconstruction, including the absence of natural anatomic infrastructure, inadequate vascularization of flaps, presence of centrifugal forces contrary to the reconstructed prominence, and dermal thickening of the available tissue. Conclusion: The technique detailed in the study maintains greater volume in the central part of the flap aiming to less flap volume loss and greater projection, with more satisfactory and long-lasting esthetic results. The short-term results are encouraging.